SERVICE OF THE CLASS II TPI CIREBON IMMIGRATION OFFICE THROUGH PARTICULAR ACTIVITIES TO YATIM PIATU CHILDREN IN THE CIREBON CITY ENVIRONMENT - M. Alvi Syahrin; Happy Herlambang (Jurnal Abdimas Imigrasi, 2020)
Orphans are a social phenomenon that is always present in society both developed and developing countries. In every region there are always orphans who need education, livelihood and others, ironically they still lack systematic and integrated assistance from the government or the environment. Orphan / orphan word means a child who loses or is left dead by his father before he goes on (Lisanul 'Arab, 12/645, al-Mu'jam al-Wasith, 2/1063) The condition of orphans causes the loss of their hopes to live their lives, especially for disadvantaged orphans. An orphan is a child whose father has died. Accommodating and caring for orphans who come from families unable to aim to help orphans in order to complete their formal education in accordance with their education. Children must get serious attention, lest they are displaced due to family economic limitations, they must be helped to rise from adversity by embracing and introducing them to education, so that we have sufficient future leaders.